Frequency of Post-Operative Bleeding after Dental Extraction among Patients on Chronic Low Dose Aspirin - Naseer Ahmed, Sunia Gul, Eruj Shuja, Arsalan Maqbool, Wasim Ibrahim, Muhammad Adil Asim (Journal of Rawalpindi Medical College, 2021)
Introduction: Anti-platelet drugs are widely used for primary and secondary prevention of cardiovascular and cerebrovascular diseases. The purpose of this study was to determine the frequency of post-operative bleeding after dental extraction among patients on chronic low-dose aspirin. Materials and Methods: This is a descriptive case series in which a total of 378 patients on low-dose aspirin of( 75-100mg) for various cardiovascular causes were included in the study. The duration of the study was from November 2016 to May 2017 total of 6 months. Results: Out of 378 cases, 247 patients (65.4%) were male while 131 patients (34.6%) were female. The mean age of the patients was calculated as 54.8±13.1 years. Regarding pre-morbid, 127 patients (33.6%) were diabetic and 109 patients (28.9%) were hypertensive. The mean duration of taking aspirin was calculated as 3.5±1.7 years. Post-extraction bleeding was noted in 16 patients (4.2%). This was statistically insignificant i.e p-value >0.005. Conclusion: We concluded that simple tooth extraction is safe in patients on a long-term maintenance dose of aspirin, without discontinuation of the drug as it doesn’t cause any significant postoperative bleeding.